The Physical and Chemical Soil Properties of The Soil Suppresive to Existence of Ganoderma boninense on The Oil Palm”. - fakhry puspika; mukhtar pinem (Jurnal Agroekoteknologi, 2018)
Basal Stem rot disease caused by Ganoderma boninense in oil palm is an important disease because it can cause damage to 100% even the death of oil palm plantation. The spread of Ganoderma boninense is influenced by internal and external factors of the plant. Internal factors of the plant include plant health and resistance to pathogen infection. As for the external factor that is the environment around the growing area, especially the condition of the soil, in this case related to soil nutrient status. This study aims to compare the soil physical properties of soil texture, and soil chemical properties is pH-H2O, pH-KCl, C-organic content, Cation Exchange Capacity (CEC) Soil, Bases cations (K, Ca, Mg and Na) Soil, soil Nitrogen content,and P-content available on soil invested and soil suppressive against Ganoderma boninense attack. The research was conducted at Oil Palm Plantation PT. Marihat, Pematang Siantar with comparative method. Samples were taken by simple random sampling method (SRS). Soil samples were analyzed at PT. Socfin Indonesia. The results showed that nutrient elements did not affect the presence of G. boninense on suppressive soils but the percentage of sand in the soil affected the spread of G. Boninense. Keywords: Ganoderma boninense, Supresive Soil, Land of Invest, Palm oil